Room temperature ferroelectricity in monolayer graphene sandwiched between hexagonal boron nitride - Fanrong Lin; Xiaoyu Xuan; Zhonghan Cao; Zhuhua Zhang; Ying Liu; Minmin Xue; Yang Hang; Xin Liu; Yizhou Zhao; Libo Gao; Wanlin Guo; Yanpeng Liu (Nature Communications)
Abstract The ferroelectricity in stacked van der Waals multilayers through interlayer sliding holds great promise for ultrathin high-density memory devices, yet mostly subject to weak polarization and cryogenic operating condition. Here, we demonstrate robust room-temperature ferroelectricity in monolayer graphene sandwiched between hexagonal boron nitride layers with a rhombohedral-like stacking (i.e., ABC-like stacking). The system exhibits an unconventional negative capacitance and record high electric polarization of 1.76 μC/cm2 among reported sliding ferroelectrics to date. The ferroelectricity also exists in similarly sandwiched bilayer and trilayer graphene, yet the polarization is slightly decreased with odd-even parity. Ab initio calculations suggest that the ferroelectricity is associated with a unique switchable co-sliding motion between graphene and adjacent boron nitride layer, in contrast to existing conventional vdW sliding ferroelectrics. As such, the ferroelectricity can sustain up to 325 K and remains intact after 50000 switching cycles in ~300000 s duration at 300 K. These results open a new opportunity to develop ultrathin memory devices based on rhombohedral-like heterostructures.